CORRELATION BETWEEN ANXIETY AND AGRESSION WITH SPECIFIC BASKETBALL PRECISION - Fadil Nika; Georgi Georgiev; Naser Rashiti; Alim Hajredini (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
The research has been conducted on 89 entities - active basketball players aged from 15 to 18. The aim of the research is to establish the level of correlation between the conative pathological factors and specific basketball precision. According to the obtained data the conclusion is that there is significant interdependence of these two sides of anthropologic status with the treated basketball players.